The potential effectiveness of probiotics in reducing multiple sclerosis progression in preclinical and clinical studies: A worldwide systematic review and meta-analysis. - Zahra Zangeneh; Mosayeb Rostamian; Hamid Motamedi; Amirhooshang Alvandi; Ramin Abiri (PLoS ONE)
Background and objective Multiple Sclerosis (MS) is an immune-mediated disease characterized by nerve cell inflammation and demyelination. The effectiveness of probiotics in reducing inflammatory damage in MS. Therefore, the aim of this systematic review and meta-analysis was the potential effectiveness of probiotics in reducing Multiple Sclerosis progression in preclinical and clinical studies. Methods PubMed, Scopus, Cochrane, and Google Scholar databases were searched using multiple relevant keywords, and screening was carried out based on the inclusion/exclusion criteria from January 2004 to August 16, 2024. Results Based on our criteria, 269 papers were obtained, and after omission of unsuitable articles, 23 full-text articles consisting of 17 animal studies and six human models were selected. It was concluded that in an experimental autoimmune encephalomyelitis (EAE) animal model, probiotics such as Bifidobacterium, Prevotella, and Lactobacillus can decrease the T helper 1 (Th1)/Th17 ratio while inducing interferon gamma (IFN-γ) and interleukin (IL)-17 levels. In all cases, probiotics can modulate immune cells and cytokines and consequently decrease EAE signs and symptoms. In all human studies, single or multiple probiotics decreased the severity of disease and changed the gut microbiota population. Conclusion Our results showed that probiotics can control the development of MS by reducing inflammatory conditions, and may have beneficial effects in the prevention and treatment of MS.